Therapeutic effect of c‐Jun N‐terminal kinase inhibition on pancreatic cancer. Issue 3 (24th January 2013) - Takahashi, Ryota; Hirata, Yoshihiro; Sakitani, Kosuke; Nakata, Wachiko; Kinoshita, Hiroto; Hayakawa, Yoku; Nakagawa, Hayato; Sakamoto, Kei; Hikiba, Yohko; Ijichi, Hideaki; Moses, Harold L.; Maeda, Shin; et al.
<x xml:space="preserve">Abstract</x> c‐Jun N‐terminal kinase (JNK) is a member of the mitogen‐activated protein kinase (MAPK) family, and it is reportedly involved in the development of several cancers. However, the role of JNK in pancreatic cancer has not been elucidated. We assessed t he involvement of JNK in the development of pancreatic cancer and investigated the therapeutic effect of JNK inhibitors on this deadly cancer. Small interfering RNAs against JNK or the JNK inhibitor SP600125 were used to examine the role of JNK in cellular proliferation and the cell cycles of pancreatic cancer cell lines. Ptf1acre/+;LSL‐KrasG12D/+;Tgfbr2flox/flox mice were treated with the JNK inhibitor to examine pancreatic histology and survival. The effect of JNK inhibition on tumor angiogenesis was also assessed using cell lines and murine pancreatic cancer specimens. JNK was frequently activated in human and murine pancreatic cancer in vitro and in vivo. Growth of human pancreatic cancer cell lines was suppressed by JNK inhibition through G1 arrest in the cell cycle with decreased cyclin D1 expression. In addition, oncogenic K‐ras expression led to activation of JNK in pancreatic cancer cell lines. Treatment of Ptf1acre/+;LSL‐KrasG12D/+;Tgfbr2flox/flox mice with the JNK inhibitor decreased growth of murine pancreatic cancer and prolonged survival of the mice significantly. Angiogenesis was also decreased by JNK inhibition in vitro and in vivo. In conclusion, activation of JNK promotes development of pancreatic cancer, and JNK may be a potential therapeutic target for pancreatic cancer.